Flood Mitigation of Nyando River Using Duflow Modelling - J. Joleha; V. Maino; A. Adyabadam; W. Zhao; S. Ke; T.H. Le (Civil Engineering Dimension, 2009)
Duflow surface water hydrodynamic model has been applied using a case study from Nyando catchment in the western part of Kenya in Africa to simulate various extreme flood behaviours and their retardation levels by using selected structural measures as flood mitigation techniques. The objective of this case study was to establish a design flood recommendable for mitigation, and to identify the most cost effective flood mitigation structure. Various design flows are simulated against the different proposed structures hence, the optimal structure can be recommended when economical, social and environmental constraints are considered in the decision making process. The proposed four flood mitigation structures flood plain extension, embankment (dykes), channel by-pass, and green-storage were simulated for 20-year recurrence interval flood to determine their individual responses in storing excess water. The result shows that building a green-storage is the best and optimal structure for flood mitigation.